2013
DOI: 10.5152/jaem.2013.009
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Inflammatory Reagents and Mortality in Patients Over the Age of 55 Hospitalised in the Internal Medicine Intensive Care Unit from the Emergency Service

Abstract: Objective: In this study, we tried to determine the relationship between inflammatory reagents, acute phase reactants, GCS, APACHE-II, SAPS-II scores and mortality of the patients over the age of 55 hospitalised inthe internal medicine intensive care unit. Material and Methods: This study was planned as a prospective, randomized study and the patients hospitalized in the intensive care unit from the emergency medicine department were enrolled in this study following the ethics committee approval. A standard da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It is an acutephase reactant and its serum level decreases with inflammation [19]. Studies have shown that there is a relationship between low albumin levels and mortality [20,21]. The ratio of CRP/albumin, which is used as a new inflammation parameter, is thought to be more related to severity of inflammation relative to albumin or CRP alone [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is an acutephase reactant and its serum level decreases with inflammation [19]. Studies have shown that there is a relationship between low albumin levels and mortality [20,21]. The ratio of CRP/albumin, which is used as a new inflammation parameter, is thought to be more related to severity of inflammation relative to albumin or CRP alone [22].…”
Section: Discussionmentioning
confidence: 99%